Studies on Global Photosynthesis and Its Regulatory Role in Natural Carbon Cycle - A. A. Ivlev (Challenging Issues on Environment and Earth Science Vol. 5, 2021)
It is shown that global photosynthesis in large systems is a generalized photosynthesis of an ensemble of the photosynthesizing organisms that make up the system at a given time. Global photosynthesis has all features that characterize the photosynthesis of individual organisms. They are: 1) the presence of two reciprocal photosynthetic processes-CO2 assimilation and photorespiration; 2) the ability to enhance or to weaken the above processes depending on the CO2 /O2 concentration ratio in the environment; 3) the ability to fractionate carbon isotopes in the metabolic processes. At the same time due to the participation of the global photosynthesis in global carbon turnover it has three features that differ it from photosynthesis of individual organism. They include: 1) a spontaneous strive to the stationary state in the ecological compensation point; 2) a stepwise nature of evolution and 3) the inability of ontogenetic changes. It is shown that it is possible to describe global photosynthesis using an equation that it is suitable for describing photosynthesis of an individual organism. The factors that form the carbon isotope composition of the sedimentary organic matter primarily depend on photosynthesis conditions, and, above all, on the CO2/O2 concentration ratio which is determined by ecologic and climatic factors in the location in the corresponding time. Thus the analysis of facial isotopic differences of sedimentary organic matter includes consideration of the specific features of its carbon isotope composition caused due to both the initial conditions of photosynthesis at the stage of existence of “living matter” and the conditions of its further transformation in sediments. From this standpoint the observed isotopic differences between organic matter and genetically related petroleum which are obviously the same age, taking into account the known mechanism of “living matter” transformation in sediments can be explained as the result of carbon isotope fractionation in post-photosynthetic metabolism in the “living matter” [1], since the mentioned difference are fully overlap by the isotopic differences of lipid and carbohydrate - protein fractions. Temporal isotope differences characterize sedimentary organic matter of different ages (related to different orogenic cycles). They are the result of different oxygen concentration arising in the atmosphere in the course of photosynthesis evolution. The regulatory role of global photosynthesis making global carbon cycle spontaneously moves towards the stationary state at the ecological compensation point.